Biographical Method in the Historical and Pedagogical Science: the Leading Trends of Formation - Hanna Belan (Pedagogical Discourse, 2013)
The article is a brief summary of the results of the research devoted to the formation and peculiarities of functioning of the biographical method in the historical and pedagogical science. The article provides consideration of the occurrence of the biographical method in the sociological and philosophical sciences, it shows the history of the term «biographical method» and its contents through the prism of the attitudes of leading domestic and foreign sociologists.The author analyzes the origins of the formation of the biographical method as a tool for scientific research of a person, sources of biographical material and their most common classifications, background and specifics of use of the biographical method in the national historical and pedagogical discourse.